Roaming the Changing Theoretical Landscape of Agricultural Communications - James F. Evans (Journal of Applied Communications, 2006)
The author comments on the role and value of dozens of theories and models he has used during more than 50 years of teaching, research, and practice in agricultural communications. The changing usage of these theories reflects changes in the scholarly foundations and practice of agricultural communications and the other disciplines to which it relates. Looking ahead, the author identifies 13 clusters of underused, new, and otherwise potentially valuable theories he believes may strengthen the contributions of this field.